(untitled) (Journal of Parents and Teachers, 1996)
Parent Schools are classified into different types, such as participatory, bureaucratic and academic, each with different approaches and objectives in family education. These schools seek to involve parents in the educational process and foster communication and joint learning. The evolution of these institutions reflects the need to adapt to current social and family dynamics.